Momordica charantia leaf extract reduces hepatic lipid accumulation and diet-induced dyslipidemia in zebrafish through lipogenesis and beta-oxidation - Semon Wu (Elsevier, 2021)
Aberrant lipid metabolism, especially dyslipidemia, has gained attention since it is closely related to various health disorders. Evidence that wild bitter melon (WBM), a natural herbal food, plays a regulatory function in lipid synthesis and accumulation has accumulated. In our study, we isolated 3β,7β,25-trihydroxycucurbita-5,23-dien-19-al (TCD) fraction of WBM leaf extract and established a dyslipidemia model to validate the effects of TCD on human adipocytes and zebrafish. After being treated with WBM, hypertrophy was inhibited in adipocytes, and lipid accumulation was diminished in zebrafish livers. In addition, lipogenic markers, including peroxisome-proliferator-activated receptor α (PPARα) and fatty acid synthase (FASN), significantly decreased when zebrafish were given WBM extract after they were given a high-fat diet. These findings explored the role of WBM in lipid metabolism and provided new insights into the pharmaceutic application of TCD in dyslipidemia.